Practicum Teachers’ Perceptions of Success in Relation to Self-Efficacy (Perceived Competence) - Anderson, Kirk; Walker, Keith; Ralph, Edwin (Alberta Journal of Educational Research, 2010)
How do student teachers gain confidence in their teaching abilities as part of their school-based practicum experience while increasing their self-efficacy from the successes of their practicum? To understand this question better, we explored preservice teachers’ post-practicum accounts of experiences of success in relation to efficacy (Bandura, 1977, 1982) with some reflection on motivational perspectives as found in self-determination theory (Ryan & Deci, 2000). Of particular interest are the findings that illuminate the views of post-practicum students toward the formative importance of school cooperating teachers, principals, and vice-principals and their lack of reference to university-based supervisors. Of more general interest are possible connections that support the need for a better understanding of intrinsic and extrinsic motivation in relation to perceived competence (self-efficacy) for novice teachers.